PERANCANGAN AKSESORI FESYEN BERBASIS ANYAMAN DAUN LONTAR DAN TENUN IKAT TRADISIONAL FLORES TIMUR: DESIGNING FASHION ACCESSORIES BASED ON PALM LEAF WEAVING AND TRADITIONAL WEAVING OF EAST FLORES - Denisa Putri Pahala; Ariani; Anita Armas; Wan Juliana Emeih Wahed; Rully A. Soeriaatmadja (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2025)
East Flores is one of the regions in East Nusa Tenggara with local potential that is worth developing, including palm leaf weaving and ikat weaving. The process of making woven palm leaves and ikat weaving cannot be separated from the diligence of Flores women. This research aims to explore these local materials in the development of modern fashion accessory products as an effort to integrate local wisdom into products that are relevant to today's needs. The practice-led research method is applied in this design through 4 (four) stages, namely: pre-design, design, design implementation, and presentation. The practice-led research produced prototypes of fashion accessory sets, namely sling bag, hand bag, and shoulder bag. The design that combines traditional techniques with modern design is expected to increase.